Albert Speer : His Battle with Truth - Sereny, Gitta (London Picador, 1995)
A biography of Albert Speer, an important figure of the Nazi High Command. An architect and an intellectual, he was seen to be a humane man, but, as Minister for Armaments, how could he not have known about the concentration camps? This book examines such moral issues about Speer and the Nazis.
Include Illustration, Notes and Index
Keywords: Speer, Albert, 1905-1981 -- Nazis -- Germany